Pengembang Media Pembelajaran Aquaponik-Induksi Elektromagnetik untuk Meningkatkan Literasi Sains Siswa Melalui Pembelajaran Berbasis STEM - Abdul Aziz Rahman (Jurnal Didaktika Pendidikan Dasar, 2020)
Science learning for middle school students is still a scary figure. The many terms, abstract concepts, and formulas make it difficult for students to learn science. This has an impact on the achievement of student learning success is low. The purpose of obtaining aquaponic-electromagnetic induction learning media is to increase students' scientific literacy through STEM-based learning. The method used in this research is the 4D R&D model ((define, design, develop, and essiminate). Data were collected using media expert content validation sheets, science literacy questions, and student response questionnaires. The results showed that the level of media validity Aquaponic-electromagnetic induction in CVI is 0.86 (valid) Scientific literacy achievement of experimental class students has a higher average score compared to students in the control class Students respond positively to electromagnetic induction aquaponic media. AIGO media can be used to improve student literacy through STEM-based learning.